2019
DOI: 10.3389/fpsyg.2019.01654
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Valence for the Processing of Facial and Verbal Stimuli—Positivity or Negativity Bias?

Abstract: Emotional valence is predominately conveyed in social interactions by words and facial expressions. The existence of broad biases which favor more efficient processing of positive or negative emotions is still a controversial matter. While so far this question has been investigated separately for each modality, in this narrative review of the literature we focus on valence effects in processing both words and facial expressions. In order to identify the factors underlying positivity and negativity effects, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 113 publications
(143 reference statements)
8
95
0
1
Order By: Relevance
“…Girls showed stronger PFC activity than boys but only when presented with positive stimuli. One review showed that preschoolers are likely to have a general positivity bias, where positive emotions are more efficiently processed than negative ones (Kauschke et al, 2019). This bias is likely due to the more sheltered, and hence more positive experiences among young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Girls showed stronger PFC activity than boys but only when presented with positive stimuli. One review showed that preschoolers are likely to have a general positivity bias, where positive emotions are more efficiently processed than negative ones (Kauschke et al, 2019). This bias is likely due to the more sheltered, and hence more positive experiences among young children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that preschool girls could be more efficient in emotional processing. Separately, studies have shown that as children develop from infancy through school age, they have a tendency to be better at processing words and faces that are positively valenced (Gao, Maurer, & Nishimura, 2010;Kauschke, Bahn, Vesker, & Schwarzer, 2019;Lepp anen & Hietanen, 2004). This would mean that stimuli with a positive emotional valence would be processed better than others.…”
Section: Factors Influencing Pfc Processing Of Videosmentioning
confidence: 99%
“…A final point to consider regarding Experiments 1a and 2 is that the FFA could have been reduced in magnitude by the very nature of our task. By asking participants to merely categorize stimuli as positive or negative, we avoided the need for them to retrieve specific emotion labels in order to make the comparison between the positive and negative categories more balanced (Kauschke et al, 2019). However, it is possible that because the muscles manipulated with the straws are linked to the specific expressions involving the mouth, this manipulation may not have had a significant impact on the type of higherlevel categorization that our participants performed.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional processing, another major cognitive function for humans, has attracted considerable interest in both the visual attention and VWM fields. In the field of visual attention, many studies have examined attentional bias toward emotional stimuli, which can be further divided into negative bias and positive bias (for negative bias, see Hansen & Hansen, 1988;Fox et al, 2000;Horstmann & Bauland, 2006;Pinkham et al, 2010; for positive bias, see: Juth et al, 2005;Williams et al, 2005;Becker et al, 2011; for reviews, see Kauschke et al, 2019;Xu et al, 2019). "Negative bias" refers to the processing advantage of negative stimuli (e.g., angry, fearful, sad, or disgusted faces) over positive stimuli (i.e., a happy face); conversely, a "positive bias" refers to the preference for positive stimuli (i.e., a happy face) in emotional processing (Kauschke et al, 2019;Yuan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of visual attention, many studies have examined attentional bias toward emotional stimuli, which can be further divided into negative bias and positive bias (for negative bias, see Hansen & Hansen, 1988;Fox et al, 2000;Horstmann & Bauland, 2006;Pinkham et al, 2010; for positive bias, see: Juth et al, 2005;Williams et al, 2005;Becker et al, 2011; for reviews, see Kauschke et al, 2019;Xu et al, 2019). "Negative bias" refers to the processing advantage of negative stimuli (e.g., angry, fearful, sad, or disgusted faces) over positive stimuli (i.e., a happy face); conversely, a "positive bias" refers to the preference for positive stimuli (i.e., a happy face) in emotional processing (Kauschke et al, 2019;Yuan et al, 2019). Interestingly, VWM studies have revealed a similar phenomenon, finding both negative and positive advantages to VWM performance (for negative bias, see Jackson et al, 2008Jackson et al, , 2009Sessa et al, 2011;Becker et al, 2014; for positive bias, see Xie et al, 2017;Spotorno et al, 2018;Curby et al, 2019).…”
Section: Introductionmentioning
confidence: 99%